Rapid Eutectic Growth Kinetics of Undercooled Nb-Si Alloys at Electrostatic Levitation State. (15th September 2022) - Li, M.X.; Wang, H.P.; Lin, M.J.; Zheng, C.H.; Wei, B.
Abstract: The rapid eutectic growth kinetics of undercooled Nb-Si alloys was investigated by using electrostatic levitation (ESL) technique combined with triggering method. For eutectic Nb-17.3 at.% Si alloy, the rapidly solidified microstructure was characterized by (Nb) dendrites and (Nb)+Nb3 Si eutectics, which was different from the master alloy composed of complete eutectic structures. The transition of primary phase from the faceted Nb3 Si phase to non-faceted (Nb) phase and the formation of complete eutectic microstructure were observed within hypereutectic Nb-18.7 at.% Si alloy with the increase of undercooling. Three distinct solidification paths leading to different microstructures and constituent phases were revealed by controlling the melt undercooling. Furthermore, the phase selection mechanism was clarified from the perspective of nucleation kinetics. Based on the experimental and analytical results, the coupled zone of (Nb)+Nb3 Si eutectic was qualitatively predicted. The final microstructures solidified at different undercoolings were all composed of the (Nb) phase and Nb3 Si phase, whose crystaline structures were both confirmed by transmission electron microscopy analysis. Besides, it was found that the volume fractions of (Nb) and Nb3 Si phases could be undercooling control adjusted by. According to the nano-indentation and Vickers micro-indentation tests, the mechanical properties varied significantly with solidification paths. Compared with the master alloy, the hardness of hypereutectic Nb-18.7 at.% Si alloy at 157 and 473 K undercoolings was decreased by 42.7 % and 9.9 %, while the fracture toughness was enhanced remarkably by 593.1 % and 144.8 %, respectively. This may provide a desirable approach for designing Nb-Si alloys with improved performances. Graphical Abstract: : Image, graphical abstract